Experimental Therapy of Paracoccidioidomycosis Using P10-Primed Monocyte-Derived Dendritic Cells Isolated From Infected Mice - Silva, Leandro B. R.; Taira, Cleison L.; Dias, Lucas S.; Souza, Ana C. O.; Nosanchuk, Joshua D.; Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Microbiology, 2019)
Paracoccidioidomycosis (PCM), a systemic mycosis prevalent in Latin America, is caused by the thermodymorphic fungi of the genus Paracoccidioides spp. Notably, a Th1 immune response is required to control PCM. In this context, dendritic cells (DCs) seem to be essential players in capture, processing and presentation of Paracoccidioides antigens to naïve T cells and their further activation. We have previously demonstrated that differentiated DCs from bone marrow cells (BMDCs), pulsed with the immunoprotective peptide 10 (P10), effectively control experimental PCM in immunocompetent and immunosuppressed mice. However, this procedure may be infeasible or limited for the therapy of human patients. Therefore, we have sought a less invasive but equally effective approach that better mimic the autologous transplant of DC in a human patient. Here, we isolated and generated monocyte differentiated dendritic cells (MoDCs) from infected mice, pulsed them with P-10, and used them in the therapy of PCM in syngenic mice. Similar to the results using BMDCs, the P10-pulsed MoDCs stimulated the proliferation of CD4+ T lymphocytes, induced a mixed production of Th1/Th2 cytokines and decreased the fungal load in the lungs of infected mice. The process of differentiating MoDCs derived from an infected host and subsequently using them for therapy of PCM is much simpler than obtaining BMDCs, and represents a more reasonable approach to treat patients infected with Paracoccidioides. The results presented suggest that P10-primed MoDC may be a promising strategy to combat complicated PCM as well as to significantly shorten the lengthy requirements for treatment in patients with this disease.